Willingness-to-Pay for Multiple Units of Eco-Friendly Wheat-Derived Products: Results From Open-Ended Choice Experiments. Issue 6 (17th August 2016) - Wongprawmas, Rungsaran; Pappalardo, Gioacchino; Canavari, Maurizio; Pecorino, Biagio
ABSTRACT: A non-hypothetical open-ended choice experiment with a multi-unit elicitation format was conducted to elicit Italian consumer willingness-to-pay (WTP) and demand schedule for new wheat-derived products that were produced by adopting an ecologically friendly post-harvest technique (high heat-treated, HHT). A sample of 270 Italian consumers were surveyed in Bologna, Catania, and Palermo in June 2014. Data were analyzed using a double hurdle model. Results suggest Italian consumers are willing to pay premium prices for HHT flour, while they prefer to pay for HHT packed bread at the same price as a conventional one. Consumers' WTP for the second, third, and more units are lower than their WTP for the first unit of product. While factors that influence consumers' decision to buy these two new products are the same, factors that affect their desired product units differ among each products. In conclusion, Italian consumers' preference for an eco-friendly label depends on the types of products.